DID REGIONAL ECONOMIC DIVERSITY INFLUENCE THE EFFECTS OF THE GREAT RECESSION?. (18th February 2016) - Deller, Steven; Watson, Philip
Abstract : Using data for U.S. counties from 2005 to 2012, we test whether higher levels of economic diversity mediated the effects of the Great Recession via four measures of stability. Spatial spillover effects are modeled by the use of the spatial Durbin estimator with heteroscedastic errors. The data generally support the central hypothesis that higher levels of diversity within a county are associated with enhanced employment stability across all counties as well as subsets of metro and nonmetro counties. Results for wage stability, however, appear to contradict our other findings. We suggest that underlying labor elasticities can bridge these apparent contradictory results. ( JEL R11, R12, O47)